2011
DOI: 10.1038/oby.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Obesity during Infancy: A Pilot Study

Abstract: More than 20% of US children between ages 2 and 5 years are overweight suggesting efforts to prevent obesity must begin earlier. This study tested the independent and combined effects of two behavioral interventions delivered to parents, designed to promote healthy infant growth in the first year. Mother–newborn dyads intending to breastfeed were recruited from a maternity ward. With a 2 × 2 design, 160 dyads were randomized into one of four treatment cells to receive both, one, or no interventions delivered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
264
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(272 citation statements)
references
References 64 publications
(63 reference statements)
4
264
4
Order By: Relevance
“…All targeted first-time mothers. Paul et al 49 reported a significant effect on weight-for-length percentiles at 12 months of age (33rd vs 50th, retention 69%; n = 22 vs 30) of an intervention comprising 3 nurse home visits targeting soothing strategies and process of solid introduction. Two other large Australian trials 47,48 have reported outcomes at ∼2 years of age.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…All targeted first-time mothers. Paul et al 49 reported a significant effect on weight-for-length percentiles at 12 months of age (33rd vs 50th, retention 69%; n = 22 vs 30) of an intervention comprising 3 nurse home visits targeting soothing strategies and process of solid introduction. Two other large Australian trials 47,48 have reported outcomes at ∼2 years of age.…”
Section: Figurementioning
confidence: 99%
“…Since the Ciampa review, 24 only 3 [47][48][49] RCTs have reported weight status after an obesity prevention intervention commencing in infancy. All targeted first-time mothers.…”
Section: Figurementioning
confidence: 99%
“…This focus for obesity prevention has gained considerable currency since this study commenced, with 1 published protocol, 28 2 pilot studies, 29,30 and 1 additional RCT published. 31 Data from the pilots and RCTs, targeting mothers and infants ,6 months of age, provide additional support for a focus on early childhood with 1 nonrandomized trial (n = 80) reporting a trend to reductions in television viewing 30 and another (n = 110) reporting a lower weight-forlength percentile in intervention children (P = .009).…”
Section: 14)mentioning
confidence: 99%
“…31 Data from the pilots and RCTs, targeting mothers and infants ,6 months of age, provide additional support for a focus on early childhood with 1 nonrandomized trial (n = 80) reporting a trend to reductions in television viewing 30 and another (n = 110) reporting a lower weight-forlength percentile in intervention children (P = .009). 29 Wen' s RCT intensive home visiting intervention 31 targeting families living in socially and economically disadvantaged areas of Sydney, Australia (n = 667), reports lower BMI and improvements in some obesitypromoting behaviors at age 2 years in the intervention compared with the control group. The previously mentioned RCT in a Cochrane review 4 (n = 43) reported evidence of lower child energy intake in the intervention group (P = .06) but no differences in BMI.…”
Section: 14)mentioning
confidence: 99%
“…While Guidelines knowledge in this study was related to the delay in the introduction of solids, the use of 'food to soothe' infant distress and promote sleep and growth is prominent in the literature, and another key modifiable obesity risk factor to address. 133,134,203,[293][294][295] Fruit and vegetable intake are fundamental indicators of a healthy diet and early exposure during infancy is associated with higher intakes during childhood. 179 Our findings that both feeding confidence and maternal self-efficacy directly affected infant fruit and vegetable intake builds on the limited studies on this relationship.…”
Section: Discussionmentioning
confidence: 99%